Non-linear effects: a new window for the primordial universe - Miranda, Tays (Cadernos de Astronomia, 2026)
Understanding the primordial universe is fundamental to connecting high-energy physics, observational cosmology, and the formation of cosmic structures. This article discusses the stochastic formalism applied to inflation and alternative collapse scenarios, highlighting its ability to access non-linear effects in the primordial density distribution. Applications to primordial black holes (PBHs), including strongly non-Gaussian curvaton scenarios, and to stochastic collapse models are presented, together with conceptual limitations and open questions.